Cenozoic sedimentary history of the northern Argentine continental slope, off Bahia Blanca, the location of the Ewing Terrace: Palaeogeodynamic and palaeoceanographic implications - Ercilla, Gemma; Schwenk, Tilmann; Bozzano, Graziella; Spiess, Volkhard; Violante, Roberto Antonio; Estrada, Ferran; Ianniccheri, Federica; Spoltore, Daniela Veronica; Alonso, Belén (Marine Geology)
New insights into the Cenozoic depositional architecture based on the seismic stratigraphy of the northern Argentine continental slope, off Bahia Blanca, allow us to reconstruct its sedimentary evolution. Five major seismic boundaries, B1 to B5 (from oldest to youngest) represent the main discontinuities bounding six seismic units: I (Eocene), II (Oligocene to early Miocene), III (middle Miocene), IV (late Miocene), V (Pliocene), and VI (Quaternary). These units comprise deposits and features (mass-flow deposits, (hemi)pelagites and/or lowdensity turbidites, contourite drifts and moats, sediment waves, and canyon deposits), of which, through time, the contourites are ubiquitous. The depositional stratigraphic architecture reflects the expansion and relocation of the contourites, which are used to divide the sedimentation history into three major periods: Eocene to Early Miocene; Middle Miocene; and Late Miocene to Recent. Each period is interpreted as having occurred in response to palaeoceanographic changes in the Southern Component Deep Water (SCDW). These changes were regulated by palaeogeodynamic variations, regionally related to the Andean orogeny and remotely related to the opening stages of the Drake Passage and Central American Seaway, as well as the consequent increases in deep-water flux to the southern Atlantic. Additionally, we also consider their interplay with local and global sea-level changes. These three main periods reveal changes in the alongslope dynamics of the SCDW on the Argentine continental slope. Fil: Ercilla, Gemma. Consejo Superior de Investigaciones Científicas. Instituto de Ciencias del Mar; España Fil: Schwenk, Tilmann. Universitat Bremen; Alemania Fil: Bozzano, Graziella. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval. Departamento Oceanografía; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Spiess, Volkhard. Universitat Bremen; Alemania Fil: Violante, Roberto Antonio. Ministerio de Defensa. Armada Argentina. ...